Transforming Mathematics Learning through Google Classroom: Analysis of Students' Mathematical Reasoning Ability and Thinking Creativity - Elya Novandi; Nining Anggeraini (Gema Cendekia Institute, 2025)
This study aims to analyze the effectiveness of transforming mathematics learning through the Google Classroom platform in improving students' mathematical reasoning abilities and creative thinking. The research method used was a quasi-experimental with a pretest-posttest control group design . The research subjects consisted of 60 students of Public Junior High Schools in Praya who were divided into two groups, namely the experimental group with Google Classroom- based learning and the control group with conventional learning. The research instruments were a mathematical reasoning ability test, a mathematical thinking creativity test, and a learning activity observation sheet. Data were analyzed using an independent t-test and N-Gain score . The results showed that there were significant differences between the experimental group and the control group in terms of improving mathematical reasoning abilities and creative thinking. The N-Gain value of the experimental group was in the medium to high category, while the control group was in the low to medium category. In conclusion, learning through Google Classroom was able to transform the mathematics learning process towards a more interactive, effective direction and encourage the development of students' reasoning abilities and creativity.